Biotransformation of Lablab purpureus during the germination process - D?az, Mar?a Felicia; Mart?n-Cabrejas, Mar?a A.; Gonz?lez, Acela; Torres, Verena; Noda, Aida (Cuban Journal of Agricultural Science, 2011)
Some changes in Lablab purpureus (dolicho) during the germination process were studied to improve its chemical composition. Three experiments were conducted and grains germinated for 96 h under different light conditions: 1 (12-h light intervals), 2 (total light) and 3 (total darkness). A one-way classification design was applied to each experiment, with four repetitions. The treatments were: 1 control (unprocessed grain), 2 (grain soaked for 6 h + 24-h germination), 3 (soaked grain + 48-h germination), 4 (soaked grain + 72-h germination) and 5 (soaked grain + 96-h germination). As the germination process moved forward, there was an increase in the weight of the germinated grains, the root longitude and the percentage of the germinated grains in the different germination assays. In all the experiments, the percentage of the germinated grains was stabilized from 72 h on. The variant of conducting the germination process under the condition of total darkness had the superior transformations, with increases in CP (30.08 vs. 26.67 %), TP (21.37 vs. 19.76 %), ADF (16.37 vs. 14.42 %) and cellulose (14.67 vs. 11.23 %), compared to the control without germination. The profile of the mineral elements showed that ash and K increased with the germination time in the three germination variants. The rest of the minerals, except phosphorous that decreased in total darkness and light, did not vary significantly. The results indicated that the procedure applied in the germination is feasible for obtaining new products in Lablab purpureus. Modifications during germination imply changes on the physico-chemical properties of this legume. Therefore, it can be considered as an effective and promising method as it enhances the function and the quality of the product. Although 72 h are enough for germination percentages superior to 80 %, germination under total darkness conditions and for 96 h is recommended for guaranteeing the bromatological quality of the product. Key words: legumes, germination, bromatology, dolicho.